First Report of Soilborne Rye Mosaic Virus in Rye in Denmark - Nielsen, S L (Plant disease, 1999)
Soilborne wheat mosaic furovirus (SBWMV)-like particles were detected in rye (Secale cereale) grown in sandy soil in West Zealand during spring 1999. Infected plants showed yellow leaf mosaic and light stunting. Electron microscopy of negatively stained crude sap preparations revealed rigid rod-shaped particles with two average lengths, 296 and 162 nm; average diameter was 23 nm. Sap-inoculation to Chenopodium quinoa and C. amaranticolor produced local leaf lesions when grown at 17°C but none when grown at 22 to 25°C. All the features agree with the description of SBWMV (1). Immunosorbent electronmicroscopy with polyclonal antiserum produced by W. Huth to furovirus-like particles isolated from rye in Germany gave a distinct decoration to particles. Light microscopy of roots cleared with 10% KOH and stained with a 0.5% solution of trypan blue in lactoglycerol revealed resting spores with a morphology and size similar to Polymyxa graminis, a furovirus vector. This is the first record of a furovirus on cereals in Denmark. The complete nucleotide sequence of the isolate was analyzed and compared with data on isolates from wheat. Sequence identity was only 74%. Therefore, the isolate was designated as soilborne rye mosaic virus. SBRMV has been recorded previously in rye and triticale in several regions of Germany (2). References: (1) M. K. Brakke. 1971. CMI/AAB Descr. Plant Viruses No. 77. (2) W. Huth. Nachrichtenbl. Dtsch. Pflanzenschutzdienstes 50:163, 1998